(3GdCeheI hGdWahdI aj eUQ GdbOjeIs - (3ajGV, eMeOs; (3COjH, SejQs; (3NWGH, eTjQIs ((3GdbGgQIs (3OGQ GdHSJGfjs, 2001)
(3fYeJ GdCSQI GdeUQjI GdbOjeI HfUjH ef GdGSJbQGQ de JYgOg GdTYhH GdbOjeI GdCNQi(B. (3hJTjQ GdcKjQ ef GdCOdI Edi GdJeGSc GdCSQj Hjf GdRhLjf ef fGMjI, hHjfgeG hHjf ChdGOgeG ef fGMjI CNQi(B. (3hbO JejRJ GdMVGQI GdeUQjI GdbOjeI NdGd MbHgG GdJGQjNjI GdeJYGbHI efP CbOe GdYUhQ HGdGgJeGe GdHGdZ HGdCeheI h GdWahdIs
(3jMJhj Ydi edMb ddUhQ GdaQYhfjI GdJj JNOe GdehVhYs
11 15
Keywords: (3GdCeheIs; (3GdMVGQI GdaQYhfjIs; (3eUQ GdbOjeIs -- (3JGQjNs